ANALYSIS OF WASTEWATER QUALITY AND PERFORMANCE EFFECTIVENESS OF WASTEWATER TREATMENT PLANT ON VANAME SHRIMP (Litopenaeus vannamei) CULTURE IN BPIU2K KARANGASEM - Sumaryati, Ni Putu; Sri Ayuni, Ni Putu; Agung Suryaputra, I Gusti Ngurah (Aurelia Journal, 2024)
Vaname shrimp (Litopenaeus vannamei) culture in BPIU2K Karangasem will produce waste from metabolism and leftover feed that contains organic material. This waste will cause environmental problems if not properly processed. This study aims to determine the quality of wastewater and the effectiveness of WWTP performance so that it can be used to generate policy recommendations for improvements in wastewater management. Water samples are taken in the morning using composite technique at five points in the IPAB inlet and outlet, each consisting of 1 liter with three repetitions.The results showed water quality of WWTP outlet from first week to third week have reached quality standard for physical parameters such as TSS and turbidity, and chemical parameters such as BOD and nitrate. However, did not reach quality standard for chemical parameters such as phosphate, H2S, nitrite, and ammonia. Removal efficiency in processing units can be used to determine the effectiveness of WWTP and will be effective if efficiency value is in the range of 60% < x = 80%. First week, WWTP in BPIU2K Karangasem showed its effectiveness on several parameters such as BOD and nitrate. Second week, the effectiveness was shown for BOD, phosphate, nitrate and ammonia. Third week, the effectiveness was shown for TSS, BOD, phosphate and H2S. The effectiveness of WWTP for each parameter differs every week due to the cultivation waste water coming from various activity units and the IPAB is still effective in treating wastewater because the five tested parameters still meet the quality standard.